2022
DOI: 10.3390/polym14245334
|View full text |Cite
|
Sign up to set email alerts
|

Curing of DER-331 Epoxy Resin with Arylaminocyclotriphosphazenes Based on o-, m-, and p-methylanilines

Abstract: As a result of this research, it was established that the chlorine atom replacement rates in hexa-chlorocyclotriphosphazene by o-, m-, and p-methylanilines’ temperatures are crucial in determining which reaction is made. The speed of reaction practically does not affect the polarity of the synthesis solvent. For the formation of fully substituted o-, m-, and p-arilaminocyclotriphosphazenes, the reaction takes 5 h and is carried out in the diglyme at its boiling temperature. The structure of the synthesized AAP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…Again, the chemical inertness and laminated structure of BN ensures long‐term stability, and its compatibility with various polymers allows seamless integration without compromising structural integrity. In contrast to phosphazenes, BN's unique properties, cost‐effectiveness, and availability further justify its preference, making it a practical choice for large‐scale applications 59,60 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Again, the chemical inertness and laminated structure of BN ensures long‐term stability, and its compatibility with various polymers allows seamless integration without compromising structural integrity. In contrast to phosphazenes, BN's unique properties, cost‐effectiveness, and availability further justify its preference, making it a practical choice for large‐scale applications 59,60 …”
Section: Introductionmentioning
confidence: 99%
“…In contrast to phosphazenes, BN's unique properties, cost-effectiveness, and availability further justify its preference, making it a practical choice for large-scale applications. 59,60 The current study emphasized on the enhancement in gas barrier, fire retardant, and antibacterial properties by BN lamination on PEMA/PVA/Ag nanocomposite thin films. The focus of the present work is to design a potential material for packaging application, leveraging the distinct advantages of each component in comparison to other polymer-based alternatives, such as chitosan.…”
mentioning
confidence: 97%
“…Compared with the known phosphonitrile-based flame retardant epoxy resin, this paper selects the metal and phosphonitrile synergistic system, the metal is dispersed in the form of coordination bond in the polyphosphonitrile, and the dispersive effect with the flame retardant is good, so as to achieve the ideal synergistic flame retardant effect. [25][26][27] The surface morphology, chemical structure, and elemental analysis was carried out using electron microscopy (SEM-EDS), infrared spectroscopy (FTIR), and x-ray photoelectron spectroscopy (XPS). The mechanical properties of Salen-PZN-Ni@BA@KH-550/ EP composites were investigated by tensile, impact, flexural and hardness tests.…”
Section: Introductionmentioning
confidence: 99%
“…It has already been reported that the hardeners types and their geometrical structures are essential parameters that determine the properties of the matrix and interphase region. [24][25][26][27][28][29][30][31][32][33][34][35][36][37] Ezquerro et al [24] used MD simulation to indicate that hardener type could change the interphase thickness; however, they could not establish a relationship between the hardener structure and interphase thickness since they only examined two kinds of hardener. Shundo et al [25] experimentally investigated the effect of the distance of the cross-linking points of the hardener, which was changed by adding different numbers of methyl groups between two cross-linking points, on the cooperative segmental dynamics in the epoxy.…”
Section: Introductionmentioning
confidence: 99%
“…It has already been reported that the hardeners types and their geometrical structures are essential parameters that determine the properties of the matrix and interphase region. [ 24–37 ] Ezquerro et al. [ 24 ] used MD simulation to indicate that hardener type could change the interphase thickness; however, they could not establish a relationship between the hardener structure and interphase thickness since they only examined two kinds of hardener.…”
Section: Introductionmentioning
confidence: 99%